Habitat use and selection patterns inform habitat conservation priorities of an endangered large carnivore in southern Europe - M de Gabriel Hernando; AA Karamanlidis; K Grivas; L Krambokoukis; G Papakostas; J Beecham (Endangered Species Research, 2021)
Understanding the habitat use and selection patterns of endangered species is essential in developing management measures that will protect critical habitat and mitigate human-wildlife conflicts. This understanding is particularly important in areas with high anthropogenic pressures. To understand the ecological role of various habitat types in the conservation of an endangered large carnivore in southern Europe, with its distinct environmental conditions and predominantly anthropogenic landscapes, we studied 18 GPS-collared brown bears Ursus arctos in Greece. We examined the use and selection of habitats according to age and sex categories and behavioral status during 5 ecologically defined seasons. Areas with rough terrain were identified as important refuge areas and were used by all bears in late hyperphagia and emergence. All bears used areas closer to human-related habitat features during the night. Habitat selection was positive for areas with rough terrain and naturalized (i.e. abandoned or not intensive) crops and areas close to water courses, while high-altitude areas and roads were avoided. The selection or avoidance of other habitats varied across bear categories and between stationary and moving behavior. We recommend that the results of the study be used to develop guidelines for species conservation and allow for prioritizing management actions that will promote the conservation of bears in Greece. In particular, the habitat use patterns provide information on how to limit interactions between humans and bears in space and/or time, while the habitat selection patterns indicate suitable habitats that should be protected/improved based on their importance and ecological role for the species.